Effect of operating conditions and screen mesh size on the performance of vermicomposting bed with automated harvester and watering system - Montepio, Roger C. (Southeastern Philippines Journal of Research and Development, 2019)
This paper presents the development of a mechanical composting bed to reduce the drudgery of the existing vermiculture production through automation of watering and harvesting system. This study also determined the effect of moisture content level, sieving speed and mesh screen size on harvesting capacity and separation efficiency. The study was laid out in factorial experiment arranged in complete randomized design (CRD). The prototype consisted of a (1) composting bed with natural aeration and screen mesh at the bottom for automatic daily harvesting of vermicast and vermicomposting leachate (VCL), (2) automated watering sprinkler system, (3) vermicast and VCL storage beneath the composting bed, and (4) control system. During harvesting, composting bed is suspended in the main frame and is driven by an electric motor creating oscillating motion, thus sieving, separating the vermicast and leaving the worm in the bed. Analysis of Variance found that all factors significantly affected the harvesting capacity. However, there was no interaction effect among the three factors on harvesting capacity and separation efficiency. Highest harvesting capacity of 74.41 g/s was obtained at lowest moisture content (40%), largest sifter size (1/4) and highest speed (310 rpm). Highest separation efficiency of 32.33 g/s was obtained at any moisture content) and largest sifter size (1/4). Daily cast and vermi leachate collected were 4 kg and 5 liters, respectively. An increase of 800 grams in worm population was recorded. The prototype had a BCR of 1.975 and IRR of 55% after 3 years of utilization.